Opodatkowanie pracy w Polsce i wybranych krajach OECD - problem klina podatkowego - Rękas, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The 21st century economy faces new economic developments that enforce changes in the labour market model and search for new competitive edges. One of the major drives of competitiveness is the taxation of labour in the broad sense, i.e. all the taxes and para-taxes levied on labour. Taxation distorts the relation between the utmost labour productivity and the labour costs/payroll, which may discourage from creating new jobs on one hand and from seeking employment on the other. The article objective is to present the cost of labour in Poland and some selected OECD countries as well as to assess the impact of tax-related labour costs on the labour market situation. This is enhanced by presenting the theoretical background of the impact of taxation on the labour market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 536-544